Adjuvant melanoma therapy with new drugs: should physicians continue to focus on metastatic disease or use it earlier in primary melanoma?. Issue 12 (December 2018) - Grob, Jean Jacques; Garbe, Claus; Ascierto, Paolo; Larkin, James; Dummer, Reinhard; Schadendorf, Dirk
Summary: It is important to differentiate between two concepts of adjuvant therapy in melanoma—what we have come to call late adjuvant and early adjuvant therapy. Early adjuvant therapy is defined as a medical intervention that is done after resection of a primary melanoma to eradicate possible undetectable minimal residual disease, whereas late adjuvant therapy is done when an overt metastatic disease (nodal or visceral) has been completely resected, to control disease better than if the same treatment were given at a later time, in the presence of multiple metastases. Early adjuvant therapy is thus a preventive treatment strategy, whereas late adjuvant therapy aims at anticipating treatment of metastatic disease. For patients with melanoma, 1-year treatment with targeted therapies and immunotherapy have only been assessed in late adjuvant settings, the outcomes of which more or less reproduce the same dramatic effect as they have in metastatic disease. However, early adjuvant therapy could provide greater benefits in terms of public health, since thin melanomas without nodal metastases are so common that they account for most deaths by melanoma. In the early adjuvant setting, a treatment course of less than 1 year might be sufficient to control the disease, with less toxicity and at reduced costs. In this Personal View, we discuss the potential benefit of short-term early adjuvant treatment in patients with stage II melanoma, with the hope that sentinel-node biopsy and the American Joint Committee on Cancer staging will soon be replaced by more relevant biomarkers to identify the most suitable candidates for early adjuvant therapy for this disease.